Prevalence of obesity and overweight in schoolchildren aged 7 to 12 years from a city in southern Brazil - Ricardo Rodrigo Rech; Ricardo Halpern; Cristine Boone Costanzi; Mauren Lúcia de Araújo Bergmann; Lidiane Requia Alli; Airton Pozo de Mattos; Leandro Trentin; Lisiane Reis Brum (Universidade Federal de Santa Catarina, 2010)
The prevalence of obesity and overweight has been increasing worldwide over the last few years. The purpose of this study was to estimate the prevalence of obesity and overweight in schoolchildren aged 7 to 12 years from a mid-sized city in southern Brazil, and to determine possible associations with socioeconomic status, aerobic fitness, dietary habits, and leisure activities (sedentary and physical activity). A cross-sectional study was conducted and 1,442 children were evaluated regarding body weight and height. Obesity was defined based on BMI for gender and age. Descriptive, bivariate and multivariate analyses were carried out between the independent variables and outcome. The prevalence of obesity and overweight was 8% (CI: 7.54-8.45) and 19.9% (CI: 19.62-20.17), respectively. Aerobic fitness (p< 0.000, PR=0.59), practicing out-of-school time sports (p=0.005, PR=1.41), sedentary habits (TV, video games and computer) (p=0.004, PR=1.50), and high socioeconomic level (p< 0.000, PR=2.64) were significantly associated with obesity and overweight in the adjusted multivariate model. Dietary habits were directly associated with obesity and overweight, but did not remain in the final multivariate model. The prevalence of obesity and overweight in this population was high and should be a matter of concern to city health authorities.